Reactions of the lithium salts of the tribenzylidenemethane dianion, diphenylacetone dianion, and related compounds - Mauser, Harald; Clark, Timothy; et al. (Journal of Organic Chemistry, 1998)
Potentially synthetically useful reactions of the dilithium salts of the title dianions have been investigated, Electrophilic quenching with a variety of reagents usually leads to the expected products in good yield. Quenching the diphenylacetone dianion with 1 equiv of trimethylchlorosilane, however, gives a good yield of 1,3-diphenylallene obtained by formal elimination of a trimethylsiloxy anion from an intermediate monoquenched monoanion salt. NMR studies, however, do not reveal the intermediacy of the 1,3-diphenyl-2-(trimethylsiloxy)allyl anion but rather suggest that the initial reaction site is at carbon, rather than oxygen, Oxidation of the dianions leads either to ring closure or dimerization for the tribenzylidenemethane dianion and to dimerization for the diphenylacetone dianion. The dimerization reactions are stereospecific, both with respect to the two new stereocenters produced and for the double bonds of the bis-silyl enol ether products if the dimeric bis-enolate dianion products are quenched with trimethylchlorosilane.